2006
DOI: 10.5860/crl.67.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Use of Circulation Statistics and Interlibrary Loan Data in Collection Management

Abstract: The authors analyzed the holdings, circulations, and interlibrary loan (ILL) borrowing requests of the English-language monograph collection at the University of Colorado at Boulder. Data for each area were mapped to conspectus subject areas, using Library of Congress Classifications, and then compared. The resulting data and subject distributions were analyzed by overall holdings, transactions per item, percentage of collection circulated, and a ratio of ILL holdings to requests. The method of analysis used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 10 publications
0
44
1
3
Order By: Relevance
“…Ochola (2002) used PEU and RBH to identify underused and overused subject collections at Baylor University. Knievel et al (2006) used "percentage of collection circulated by subject" and "average number of transactions per item per subject" to inform collection development and assessment at the University of Colorado at Boulder and also included interlibrary loan statistics. Cheung et al (2011) examined circulation of books at Lingnan University in Hong Kong over a 15-year period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochola (2002) used PEU and RBH to identify underused and overused subject collections at Baylor University. Knievel et al (2006) used "percentage of collection circulated by subject" and "average number of transactions per item per subject" to inform collection development and assessment at the University of Colorado at Boulder and also included interlibrary loan statistics. Cheung et al (2011) examined circulation of books at Lingnan University in Hong Kong over a 15-year period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that almost 65% had been checked out at least once, but books that did not circulate within the first few years of purchase were unlikely to circulate at all. Knievel et al (2006) urge librarians to use detailed circulation data and statistics to inform "evidence-based decision making" in this era of decreasing library budgets. Ten years earlier, Carrigan (1996) had reported that despite increasing demand for libraries to provide more resources with lower budgets and growing pressures of fiscal accountability, most libraries did not use circulation data to inform collection management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Librarians must be judicious in their selection process. The abundant funding of the 1990's is no longer occurring, meaning that librarians' approach to collection development must be strategic and purposeful (Knievel, Wicht, & Connaway, 2006). Based on this evidence, the following exercise was undertaken to assess the strength of our current collection and the potential absence of core texts published prior to the library's opening in 1994.…”
Section: Problemmentioning
confidence: 99%
“…The subject areas designated by the conspectus system were "broad subject classifications based on the Library of Congress classification system." 13 16 devised a method of quantitative evaluation using WorldCat's FirstSearch interface to see whether his library's holdings were mainly books held by many other libraries or books held by few. This method could identify areas of specialization in one's library.…”
mentioning
confidence: 99%